2016
DOI: 10.14260/jemds/2016/510
|View full text |Cite
|
Sign up to set email alerts
|

Role of Medical Thoracoscopy in the Diagnosis of Pleural Empyema

Abstract: BACKGROUNDMedical thoracoscopy is a minimally invasive procedure that allows access to the pleural space using a combination of viewing and working instruments. The main diagnostic and therapeutic indications for Medical Thoracoscopy are difficult pleural effusions, empyemas and pneumothorax. It can also be effectively used in the diagnosis and management of early stages empyema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…These results are in agreement with that done by Bhatt et al [15], who studied the diagnostic role of MT in empyema and reported that MT is a simple, safe, minimally invasive, less painful, and efficient diagnostic procedure. It decreases the morbidity and length of hospitalization in loculated empyema.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with that done by Bhatt et al [15], who studied the diagnostic role of MT in empyema and reported that MT is a simple, safe, minimally invasive, less painful, and efficient diagnostic procedure. It decreases the morbidity and length of hospitalization in loculated empyema.…”
Section: Discussionsupporting
confidence: 93%